PROTOTYPE ALAT PENDETEKSI GEMPA MENGGUNAKAN SENSOR ACCELEROMETER ADXL335 BERBASIS INTERNET OF THINGS - Lenni, Lenni; Ardiansyah, Fauzy (Jurnal Teknik Elektro, 2024)
An earthquake is a natural phenomenon that can be caused either by human activity or by natural events. A disaster is an unpredictable natural event. Of the few earthquakes that have ever occurred, many citizens are always late to save themselves or evacuate to a safe place because of the late notification of earthquake information that occurred at the location. One of the solutions to minimize such impacts is to create a prototype earthquake detector using an Internet of Things-based adxl335 accelerometer sensor. It works from an accelerometersensor that detects vibrations or shocks, then processed by ESP32 as a microcontroller and Telegram as an Internet of Things based monitoring dashboard through notifications sent by a telegram bot. Buzzer and LED indicator lights are connected to the telegram application to monitor realtime earthquake warnings. The richter scale value will be displayed on the I2C LCD as a direct monitor for warning information.